(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Poverty reduction and economic growth can be sustained only if natural resources are managed on a sustainable basis. Greening rural development can stimulate rural economies, create jobs and help maintain critical ecosystem services and strengthen and strengthen climate resilience of the rural poor. Conversely, environmental challenges can limit the attainment of development goals. The Approach Paper to the Twelfth Five Year Plan notes that “as the economy gains the capacity to grow rapidly, it will come up against the constraint of limitations of natural resources and then need to exploit these in a sustainable manner”.1Recognizing the national and global imperatives for regenerating natural resources and conserving ecosystems, the Ministry of Rural Development requested UNDP to examine the environmental implications of its schemes and assess the potential of these schemes to deliver green results. The paper defines ‘green’ outcomes for major RD schemes, reviews the design and evidence from the field to highlight potential green results and recommends steps to improve green results.